Mechanical and biological evaluations of hydroxyapatite composite for orthopedic applications / Saeid Baradaran - Baradaran, Saeid (2015)
Hydroxyapatite (HA) has received wide attention in orthopedics, due to its biocompatibility and osseointegration ability. Despite these advantages, the poor mechanical properties of HA often results in rapid wear and premature fracture of implant. Hence, there is a need to improve the mechanical properties of HA without compromising its biocompatibility. The aim of the current research is to explore the potential of metal ion doping and graphene nanosheets (GNS) as reinforcement to HA for orthopedic implants. HA/reduce graphene oxide (rGO) and Ni doped HA/Graphene nano platelet (GNP) are synthesized by hydrothermal and chemical precipitation and characterized by XRD, FT-IR, EDAX, FESEM and Raman spectroscopy. HA/reduce graphene oxide (rGO) and Ni doped HA/ Graphene nanoplatelet (GNP) powder are solidified by hot iso-static pressing, and investigated for their mechanical and biological behavior. In this aspect, rGO, GNP and metal ions reinforcement improve the mechanical properties of HA for free standing composites. In case of nHA/rGO, the fracture toughness and modulus elasticity improves 40% and 86% by wt.%1.5 GNS and hardness increases 32% by wt.%1.0 GNP in compare to HA. In another case (HA-Ni/GNP), microhardness, fracture toughness and elastic modulus of 6%Ni doped HA were improved 55% , 60% and 121% in 6% doping of Ni and also 75%, 164% and 85% in 1.5Ni6, respectively. Both cases have demonstrated a positive influence on the proliferation, differentiation and matrix mineralization activities of osteoblasts, during in-vitro biocompatibility studies in presence of GNS.